Nutritional diagnosis by Dris method of the cultivars coffee in the northern region of Paraná, Brazil - Silva, Ricardo Augusto; Creste, José Eduardo; Tiritan, Carlos Sérgio; Guerra, Wellington Eduardo Xavier; Ecker, Arney Eduardo do Amaral (Coffee Science - ISSN 1984-3909, 2015)
Due to the lack of knowledge on the nutritional status of the coffee shrub, DRIS method was introduced in coffee culture in the northern region of the state of Parana, Brazil. Current research aimed at establishing a data base for DRIS guidelines in coffee culture and introducing other parameters for the rational and balanced application of fertilizers. Assay was performed between February 2011 and February 2012 (Harvest 2011/201) in coffee plantations in the municipality of Pitangueiras PR Brazil, 23o 14’ 03” S and 51o 35’ 06” W; altitude 600 m. Leaf samples from 75 coffee shrub lots were retrieved from 69 plantations, featuring cultivars IAPAR 59, IPR 98, IPR 99, Catuaí, Mundo Novo and Tupi. DRIS norms were established for the nutritional diagnosis of the coffee shrub for the northern region of the state of Paraná through the criterion of productivity at 55 sacks ha-1. Data revealed that potassium constituted the highest deficiency, followed by Cu and Zn. Fe, S and Mn had excessive rates with regard to parameters at regional level.